Structural, electrical and mechanical behavior evaluation of palladium doped diamond like carbon thin films - M.I. Khan; Imran Rasheed; M.A. Naeem; Shahbaz Majeed; Ghulam M. Mustafa; Mahvish Fatima; Asif Mahmood; Waheed Al-Masry; Munawar Iqbal; Nessrin A. Kattan; Arif Nazir (Journal of Materials Research and Technology, 2020)
Pure and palladium (Pd) doped Diamond-like carbon (DLC) thin films have been deposited on glass substrates by using KrF Excimer laser having 248 nm wavelength. The doping concentration of Pd in DLC is 0%, 0.5%, 1.0%, 1.5% and 2.0%. Internal structure, surface morphology, mechanical and electrical characteristics have been carried out by Raman spectroscopy, scanning electron microscopy (SEM), Vickers hardening and four point probes, respectively. Using Raman spectra an improved graphitic behavior of DLC has been observed with increase of Pd contents. Some nano rods were observed at the surface of pure and Pd doped DLC thin films. With increase of Pd concentration in DLC, initially there is an accumulation of particles is observed and when the doping concentration is high i.e. at 2%, cracks formation takes place. The electrical resistivity is decreased by adding Pd into DLC thin films. Further, doping of Pd decreased the hardness of films. These characteristics of Pd doped DLC with increased hardness and electrical conductivity make it potential candidate for electronic devices. Also, doping enhance the graphitic behavior, therefore this material can be used for anti-bacterial and anti- cancerous activities.